Structural evolution of graphene in air at the electrical breakdown limit. (April 2016) - Son, Jangyup; Choi, Minkyung; Choi, Heechae; Kim, Sang Jin; Kim, Seungchul; Lee, Kwang-Ryeol; Vantasin, Sanpon; Tanabe, Ichiro; Cha, Jongin; Ozaki, Yukihiro; Hong, Byung Hee; Yang, In-Sang; et al.
Abstract: In application of graphene to real electronics, understanding the mechanism of the electrical breakdown of the graphene in harsh environments should precede many activities in tamed conditions. In this article, we report the unusual structural evolution of microbridge graphene in air near the electrical current-breakdown limit. In-situ micro-Raman study revealed that Joule heating near the electrical breakdown gave rise to a substantial structural evolution: a previously unknown broad amorphous-like and partially reversible phase at an on- and off-current of ∼3.0 × 10 8 A/cm 2, which finally drove the phase to the electrical current-breakdown. Our calculations suggest that the phase originates from the broken symmetry caused by defect formations during Joule heating. In particular, these formations are bonds of carbon-oxygen and vacancies-oxygen. A collection of energetically favorable vacancies-oxygen pairs results in porous graphene, and its evolution can be the key to understanding how the breakdown starts and propagates in graphene under high current density in air.